Structural magnetic resonance imaging can identify trigeminal system abnormalities in classical trigeminal neuralgia - Danielle DeSouza; Danielle DeSouza; Danielle DeSouza; Mojgan Hodaie; Mojgan Hodaie; Mojgan Hodaie; Mojgan Hodaie; Karen Deborah Davis; Karen Deborah Davis; Karen Deborah Davis; Karen Deborah Davis (Frontiers Media S.A., 2016)
Classical trigeminal neuralgia (TN) is a chronic pain disorder that has been described as one ofthe most severe pains one can suffer. The most prevalent theory of TN etiology is that the trigeminal nerve is compressed at the root entry zone (REZ) by blood vessels. However, there is significant evidence showing a lack of neurovascular compression (NVC) for many cases of classical TN. Furthermore, a considerable number of patients who are asymptomatic have MR evidence of NVC. Since there is no validated animal model that reproduces the clinical features of TN, our understanding of TN pathology mainly comes from biopsy studies that have limitations. Sophisticated structural MRI techniques including diffusion tensor imaging provide new opportunities to assess the trigeminal nerves and CNS to provide insight into TN etiology and pathogenesis. Specifically, studies have used high-resolution structural MRI methods to visualize patterns of trigeminal nerve-vessel relationships and to detect subtle pathological features at the trigeminal REZ. Structural MRI has also identified CNS abnormalities in cortical and subcortical gray matter and white matter and demonstrated that effective neurosurgical treatment for TN is associated with a reversal of specific nerve and brain abnormalities. In conclusion, this review highlights the advanced structural neuroimaging methods that are valuable tools to assess the trigeminal system in TN and may inform our current understanding of TN pathology. These methods may in the future have clinical utility for the development of neuroimaging-based biomarkers of TN.